2019
DOI: 10.2147/ppa.s223837
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prevalence and Risk Factors of Immunosuppressant Nonadherence in Heart Transplant Recipients: A Single-Center Cross-Sectional Study</p>

Abstract: BackgroundImmunosuppressant nonadherence (INA) has been shown to affect outcomes after solid organ transplantation. The aim of the present study was to determine the prevalence of INA in heart transplant recipients and the associated risk factors of INA.MethodsAdult heart transplant recipients who firstly received heart transplantation (discharged for at least 3 months) were consecutively enrolled. Immunosuppressant adherence was assessed using the Basel Assessment of Adherence with Immunosuppressive Medicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The BAASIS is reliable, valid, short, simple to use, and sensitive to the taking and timing of immunosuppressive drugs 22 . It has been previously used to evaluate nonadherence to immunosuppressive medication among heart, liver, and lung transplant recipients 23–26 . Its score is reliable, as shown by its total Cronbach alpha coefficient of .697 26 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The BAASIS is reliable, valid, short, simple to use, and sensitive to the taking and timing of immunosuppressive drugs 22 . It has been previously used to evaluate nonadherence to immunosuppressive medication among heart, liver, and lung transplant recipients 23–26 . Its score is reliable, as shown by its total Cronbach alpha coefficient of .697 26 …”
Section: Resultsmentioning
confidence: 99%
“…22 It has been previously used to evaluate nonadherence to immunosuppressive medication among heart, liver, and lung transplant recipients. [23][24][25][26] Its score is reliable, as shown by its total Cronbach alpha coefficient of .697. 26…”
Section: Basel Assessment Of Adherence To Immunosuppressive Medicatio...mentioning
confidence: 98%
“…22 Findings based on our calculated nonadherence risk outcome are consistent with other studies that have examined the influence of number of medications on immunosuppressant adherence among kidney and other organ recipients. 20,23 We also found that increased time since transplant was associated with lower risk of immunosuppressant nonadherence; evidence in the literature of the effect of time since transplant is mixed. 19 Differences in adherence based on insurance status were surprising, in that participants in our study with dual private/public coverage were particularly vulnerable to nonadherence risk.…”
Section: Discussionmentioning
confidence: 62%
“…It is possible that participants in our sample who struggled with a greater number of comorbid conditions found taking related medications more burdensome, which has been observed to affect adherence among other organ recipients. 20 This might extend to depression as well; there is some evidence that higher levels of depression are linked with a greater number of comorbid conditions. 21 Health literacy was also significantly related to poorer regimen adherence in our study, and as a modifiable SDOH, this may be informative for intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Nonadherence can be either deliberate or unintentional and include such events as not taking the medication as often as required, not in the exact dose and/or at the correct times (O'Carroll et al, 2006). The prevalence of immunosuppressant non-adherence can vary from 2 to 67% in solid organ transplant recipients (Martin and Gabardi, 2009;Zhang et al, 2019). The highest rate of immunosuppressant non-adherence was found in kidney transplant recipients with a prevalence of 36-55% (Gokoel et al, 2020), while that in adult heart transplant recipients is 34.1-41.1% (Leven et al, 2017) and 15-40% in liver transplants (Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%